Penggunaan GIS Untuk Pemetaan Sebaran Jenis, Peran Dan Keanekaragaman Arthropoda Tanah Pada Ordo Tanah Inceptisol Yang Ditanami Tembakau - Swardana, Ardli; Fathurrohan, Bagus Irham; Maesaroh, Syti Sarah (Jurnal Agro Wiralodra, 2024)
Tobacco cultivation in Garut Regency has the potential to be developed due to favorable environmental conditions. Cultivation activities that are less environmentally friendly can cause changes in the composition and role of soil arthropods. This study aims to identify the types, roles, and diversity of soil arthropods using GIS. The research method used in this research is spatialized descriptive-quantitative. The observation locations are in two locations, namely Karyasari Village and Sukasenang Village, both of which are in Banyuresmi District, Garut Regency. The location was chosen based on the land planted with tobacco plants. The main parameters observed in this study were the identification of the types, roles, and diversity values of soil arthropods. Diversity analysis uses the Shannon-Wienner index. The results of the study showed that the number of orders and species in Karyasari Village was lower when compared to Sukasenang Village. This also occurred in the composition of the number of roles of soil arthropods in Sukasenang Village, which was more complete when compared to Karyasari Village, including the medium category. The land in Karyasari Village can be said to be less stable when compared to Sukasenang Village.